Formação continuada da educação especial para professores dos anos finais do ensino fundamental: Uma proposta com ênfase nas práticas pedagógicas inclusivas na UEB Jornalista Neiva Moreira - FRAZÃO, Thays Nayara (2023)
This research aimed to investigate Continuing Education in the area of Special Education for teachers in the ordinary class of the Final Years of Elementary School in order to reflect on inclusive pedagogical practices through interventions in a virtual learning room at Elementary School Basic Teaching Unit (UEB) Journalist Neiva Moreira. To this end, the research was a qualitative approach from an exploratory study, with the purpose of an applied nature, with the proposition of a product to the institution that deals with the implementation of a virtual room for Continuing Education, learning and inclusion, to foster inclusive pedagogical practices within the scope of elementary school. The procedures used were bibliographic, documentary and field supported by the principles of Case Study type research. The instruments used for data collection consisted of: semi-structured interview and systematic observation. The participants involved totaled 11, being seven teachers from the Final Years of ordinary education, among these: three female teachers and four male teachers; one school coordinator, one superintendent of the Final Years, one Superintendent of Special Education and one person responsible for the Advanced Center for Education Support (CAAED). The presentation of results and data analysis took place from three categories: inclusive pedagogical practices, Continuing Education of teachers from Municipal Secretary of Education (Semed) and from the school, besides resources used in teaching. The results regarding the “inclusive pedagogical practices” have demonstrated weaknesses regarding participants; knowledge of inclusion and that there is a need for strategies of formations to improve classroom performance, as in the Continuing Education category found the absence of Continued Formations for teachers UEB Journalist Neiva Moreira specifically to effectively meet the students target audience of special education. In the category that deals with the resources used in teaching, the lack of technological support and active methodologies for the elaboration of materials and pedagogical resources were exposed. From the main findings of the research, it was evident the need for improvement in the Continuing Education of teachers in the school itself and the school network that reverberates in (more) inclusive pedagogical practices, as well as providing participating teachers new possibilities for participation and learning by means of the product of the study: The Virtual Room of Continuing Education, Learning and Inclusion.